The Abandoned Farmer - Preston, Sydney Herman, 1858-1931 (Salt Lake City, UT : Project Gutenberg, 2015)
"The Abandoned Farmer" by Sydney H. Preston is a novel written in the early 20th century. The story revolves around Henry and Marion Carton, a city couple who, after a doctor's recommendation for their son Paul$1 (Bs health, decide to leave urban life behind and seek a rural existence. The book explores their journey into the complexities of country life, their household dynamics, and the challenges that come with adapting to farming. At the start of the novel, we are introduced to Henry, Marion, and their delicate son, Paul. A visit to the doctor reveals that Paul should spend time in the countryside for his health, prompting the couple to consider relocating. As they discuss the move, the challenges of transitioning from city living to rural life become apparent, revealing the differences in their perspectives on practicality and ideals. The first chapter delves into their motivations, personal reflections, and the tender dynamics of their family, setting the stage for their adventures and misadventures as they try to create a new life in the country. (This is an automatically generated summary.)s
Release date is 2015-03-10
E-text prepared by Martin Pettit and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Humorous stories; Country life -- Fiction; Canadian fiction; Families -- Fiction